Penyelidikan Penggunaan konkrit buih sebagai bahan penimbusan untuk menggantikan pasir - Yeong, C.L (University Malaysia Sarawak, UNIMAS., 2009)
Foam concrete has been a subject of interest in Civil Engineering field for many years. Yet, so far there are not much research had been done on the possibility of using foam concrete as a backfill material. Due to the properties of foam concrete which is light in weight and thus low in density, this research has been designed in a way that the feasibility of using foam concrete as a foundation is carried out.